A garden eden : masterpieces of botanical illustration = Ein garten eden : meisterwerke der botanischen illustration = Un jardin d' eden : chefs-d'ceuvre de l'illustration botanique - Lack, H. Walter (Cologne, Germany : Taschen GmbH, 2016)
Animals and nature in art (still life, landscapes and seascapes, et cetera). Heaven on earth: Botanical masterworks from the National Library of ViennaIn pursuit of both knowledge and delight, the craft of botanical illustration has always required not only meticulous draftsmanship but also a rigorous scientific understanding. This fresh TASCHEN edition celebrates the botanical tradition and talents with a selection of outstanding works from the National Library of Vienna, including many new images. From Byzantine manuscripts right through to 20th-century masterpieces, through peonies, callas, and chrysanthemums, these exquisite reproductions dazzle in their accuracy and their aesthetics. Whether in gently furled leaves, precisely textured fruits, or the sheer beauty and variety of colors, we celebrate an art form as tender as it is precise, and ever more resonant amid our growing awareness of our ecological surroundings and the preciousness of natural flora.
Includes bibliographical references.
Parallel text in English, German and French.
Keywords: v; Botanical illustration catalogs -- Catalogs; Plants in arts catalogs -- Catalogs; Flowers in art -- Catalogs; Leaves in art catalogs -- Catalogs; Plants -- Pictorial works